A NOTE ON THE PLANKTON OF A FRESHWATER IMPOUNDMENT IN KARNATAKA - Rao, D S Krishna (Indian Journal of Fisheries, 2011)
The quiilitiitivc and quantitative composition of plankton in the Ivarukandapuia tank. Bangalore District, during the period January 1981 through January 1982, are discussed in relation to physico-chemical parameters. Phytoplankton was in sparss density with the number ranging from nil to 6000|m and qualitatively poor. Zooplankton was predominant throughout the year with the number fluctuating between 21,000 and 3,50,bOO|m^, exhibiting bimodality, with a primary peak in February and a secondary one in August. The low production of plankton as a whole was due to turbidity of waters and low nutrient of both soil and water